Effect of herbicides on increase in productivity of groundnut (Arachis hypogaea) - MOHANTY, S K; PANI, S K; KAR, M; BAISAKH, N (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during winter season of 1993-94 at Bhubaneshwar to assess the efficacy of herbicides on groundnut (Arachis hypogaea L.) and to compare their relative effect with that of hand-weeding. Fluchloralin as well as pendimethalin bad better effect than hand-weeding in respectÂ  of most of the growth parameters. However, maximum augmentation in yield was obtained in fluchloralin (0.7S kg ai/ha) followed by pedimethalin and hand-weeding. The protein and oil yields were also found highest in fluchloralin treatment.